Power shapes power construal: the mediating role of entitlement - Wang, Xinyue; Liu, Jingyuan; Li, Hong (Frontiers in Psychology, 2024)
Introduction This article investigates the effect of power on power construal through psychological entitlement as a mediator across three empirical studies (N = 895). Methods We examine how people in powerful and powerless conditions construe power, with psychological entitlement as a key mediator. Results We uncover a nuanced association whereby people in powerful conditions predominantly adopt socialized orientations to construe power, whereas in powerless conditions, people tend to construe power as a paradox. These different construals appear to be significantly mediated by the perceived psychological entitlement of powerful people. Discussion Our research provides insights into the nature of power by revealing two interesting phenomena: the powerful people prosocial gloss and the powerless people paradox. By extending the theory of culturally nurtured power concepts to include the impacts of power itself on power construal, our research offers insights into how power is construed differently based on one’s power position (i.e., with or without power), enriching our understanding of power. This exploration broadens theoretical frameworks and implicates practical considerations in organizational and social settings.